(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Data on 103 rare or overlooked lichenized, lichenicolous and lichen-allied fungi from Ukrainian Carpathians are provided. Among them, 29 lichen-forming fungi, three lichenicolous fungi and one (facultatively lichenicolous) algicolous fungus are new to Ukraine: Absconditella sphagnorum, Adelolecia kolaensis, Arthonia muscigena, Arthrorhaphis aeruginosa, Biatora albohyalina, Brodoa atrofusca, Bryodina rhypariza, Calicium pinastri, Caloplaca fuscorufa, C. isidiigera, Carbonea invadens, Catillaria croatica, Cryptodiscus gloeocapsa, Cystocoleus ebeneus, Epigloea medioincrassata, Gyalidea fritzei, Lecidea pullata, Lecidella patavina, Melaspilea granitophila, Micarea turfosa, Monodictys epilepraria, Opegrapha corticola, Phaeographis inusta, Polyblastia schaereriana, Protothelenella sphinctrinoides, Psilolechia clavulifera, Pycnora leucococca, Rinodina orculata, Sclerococcum griseisporodochium, Thelocarpon robustum auct. brit., non Eitner, Trapeliopsis glaucolepidea and Vezdaea stipitata. There is no reliable/confirmed record of Brodoa intestiniformis from Ukrainian Carpathians; all herbarium samples named as such proved to be B. atrofusca or were misidentified. All references to Chaenotheca cinerea in checklists which consider Ukraine are erroneous or very dubious, thus our record is the first reliable for Ukraine, as are our collections of Caloplaca conversa and Lecidea sphaerella. Although Multiclavula mucida and Schaereria fuscocinerea are absent from lichen checklists of Eastern Carpathians and Ukraine, they have been reported from the territory in previous published Czech or Ukrainian papers. Pertusaria ophthalmiza was recorded from Ukraine, incorrectly as P. multipuncta, but the presence of true P. multipuncta (Turner) Nyl. (non auct.) is uncertain in Ukraine. Phaeographis dendritica and Biatora meiocarpoides should be excluded from upcoming lists of Ukrainian lichens; the former is incorrectly reported from Ukrainian Carpathians and the latter is a synonym of Micarea lithinella.